Reactive Oxygen Species, Endoplasmic Reticulum Stress and Mitochondrial Dysfunction: The Link with Cardiac Arrhythmogenesis - Tse, Gary; Yan, Bryan P.; Chan, Yin W. F.; Tian, Xiao Yu; Huang, Yu (Frontiers in Physiology, 2016)
Background: Cardiac arrhythmias represent a significant problem globally, leading to cerebrovascular accidents, myocardial infarction, and sudden cardiac death. There is increasing evidence to suggest that increased oxidative stress from reactive oxygen species (ROS), which is elevated in conditions such as diabetes and hypertension, can lead to arrhythmogenesis. Method: A literature review was undertaken to screen for articles that investigated the effects of ROS on cardiac ion channel function, remodelling and arrhythmogenesis. Results: Prolonged endoplasmic reticulum stress is observed in heart failure, leading to increased production of ROS. Mitochondrial ROS, which is elevated in diabetes and hypertension, can stimulate its own production in a positive feedback loop, termed ROS-induced ROS release. Together with activation, mitochondrial inner membrane anion channels, it leads to mitochondrial depolarization. Abnormal function of these organelles can then activate downstream signalling pathways, ultimately culminating in altered function or expression of cardiac ion channels responsible for generating the cardiac action potential (AP). Vascular and cardiac endothelial cells become dysfunctional, leading to altered paracrine signalling to influence the electrophysiology of adjacent cardiomyocytes. All of these changes can in turn produce abnormalities in AP repolarization or conduction, thereby increasing likelihood of triggered activity and reentry. Conclusion: ROS plays a significant role in producing arrhythmic substrate. Therapeutic strategies targeting upstream events include production of a strong reducing environment or the use of pharmacological agents that target organelle-specific proteins and ion channels. These may relieve oxidative stress and in turn prevent arrhythmic complications in patients with diabetes, hypertension and heart failure.